2015
DOI: 10.1007/s00394-015-0971-5
|View full text |Cite
|
Sign up to set email alerts
|

MnSOD and CAT polymorphisms modulate the effect of the Mediterranean diet on breast cancer risk among Greek-Cypriot women

Abstract: Our results demonstrate that the antioxidative effects of the MD against BC risk may be enhanced by the wild-type alleles of the MnSOD or CAT SNPs among Greek-Cypriot women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…In the same year, Kocabaş et al (35) also carried out another case-control study, including 103 patients and 84 controls, demonstrating a similar result to Bergman et al (32); however, no significant difference about the risk of allele T and C was observed. Furthermore, the majority of other publications suggested that the SOD2 Val-16Ala could not increase or decrease breast cancer risk and survival (26)(27)(28)(29)(30)(31)33,34,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same year, Kocabaş et al (35) also carried out another case-control study, including 103 patients and 84 controls, demonstrating a similar result to Bergman et al (32); however, no significant difference about the risk of allele T and C was observed. Furthermore, the majority of other publications suggested that the SOD2 Val-16Ala could not increase or decrease breast cancer risk and survival (26)(27)(28)(29)(30)(31)33,34,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, two relative meta-analyses were published in 2011 and 2012, but all of the included studies and cohorts were carried out before 2009 (52,54). From 2010-2016, there were another eight studies published, and so the present meta-analysis was conducted (43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…11 Nonetheless, additional studies suggest that fruits and vegetables may minimize the risk of diseases associated with Val16Ala-SOD2 SNP. [12][13][14][15] Because fruits contain a large number of polyphenols and micronutrients with antioxidant action, two studies involving in vitro analysis were conducted to evaluate the effect of isolated molecules (resveratrol and seleno-L-methionine, SeMet) on oxidative modulation of peripheral-blood mononuclear cells (PBMCs) with different Val16Ala-SOD2 genotypes. 16,17 The results suggested that, mainly SeMet can exert a major antioxidant effect in both homozygous genotypes by modulation of GPX and of other antioxidant molecules.…”
Section: Figurementioning
confidence: 99%
“…The higher iron and low vegetable intake in TT (Val/Val) carriers was associated with increased risk of aggressive prostate cancer (Choi et al 2008 ). In Greek-Cypriot women, high fish and vegetable intake reduced breast cancer risk in TT genotypes (Kakkoura et al 2015 ). As for other diseases, the TT genotype was associated with CHD in females but not males (Jones et al 2010 ), and with CHD in hereditary hemochromatosis patients (Valenti et al 2004 ), thus suggesting a GxG impact.…”
Section: Gene-environment Interaction and Other Factorsmentioning
confidence: 99%